2012
DOI: 10.1097/jom.0b013e31825b1bfc
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Job Stress and Obesity in Nurses With Favorable and Unfavorable Work Schedules

Abstract: Considering impacts of WSs on obesity and potential obesity-related health outcomes, healthful scheduling should be provided to nurses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 37 publications
0
36
0
3
Order By: Relevance
“…31 Shift work or unhealthy work schedules may also represent barriers. 17,22,41 For example, access to healthy foods may be limited for nurses working nights and weekends because cafeterias may be closed and nurses may, out of necessity, rely on vending machines for meals and snacks. 42 Nurses who work night shifts report that disruptions in their circadian rhythms affect their ability to exercise and eat a healthy diet.…”
Section: Barriers To Health-promoting Behaviorsmentioning
confidence: 99%
“…31 Shift work or unhealthy work schedules may also represent barriers. 17,22,41 For example, access to healthy foods may be limited for nurses working nights and weekends because cafeterias may be closed and nurses may, out of necessity, rely on vending machines for meals and snacks. 42 Nurses who work night shifts report that disruptions in their circadian rhythms affect their ability to exercise and eat a healthy diet.…”
Section: Barriers To Health-promoting Behaviorsmentioning
confidence: 99%
“…Research regarding workplace factors that contribute to health‐promoting behaviours in nurses has been limited. While research has examined the relationship between unfavourable work schedules such as long hours, night shifts and/or variable shifts with stress, obesity and sleep (Caruso, ; Han et al, ), these studies did not examine whether unfavourable schedules contribute to nurses’ own participation in health‐promoting behaviours. No published studies have examined how much nurses sit during the work day.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, increased work burden may prevent nurses from establishing control over work. Some studies pointed out that control over work, requiring the jobs done with minimum sources and in the shortest time, causes nurses to experience stress, too (Yada et al, 2015;Han, Trinkoff, Storr, Geiger-Brown, Johnson & Park, 2012;Ozen, 2013;Johnston, Jones, Charles, McCann & McKee, 2013). However; nurses may face frustration and disappointment when they cannot provide a care of high quality they aim at and cannot answer patients' demands due to high work burden; which eventually leads to stress, too.…”
Section: Discussionmentioning
confidence: 99%
“…Yet; the current study presented that two in five nurses were not employed at the department where they requested to work and therefore underwent high level of stress; which indicated that the nurses were not backed up and supported in managerial/administrative sense. Some studies argued that lack of support from managers and administrators may lead to job stress (Han et al, 2012;Ozen, 2013) and the study of Ergun and Celik (2015), suggested that to support employees is effective upon decreasing job stres.…”
Section: Discussionmentioning
confidence: 99%